The Name of a Queen
V, 203 p.
Keywords: Itinerarium ad Windsor concerns a central question of the Elizabethan era: Why should a woman be allowed to rule with the same powers as a king? The man who poses this controversial question within Itinerarium is none other than Queen Elizabeth's powerful favorite Robert Dudley, Earl of Leicester. On hand to provide answers are the statesman and poet Thomas Sackville, Lord Buckhurst, and William Fleetwood antiquary, Recorder of London, and dutiful chronicler of their 1575 conversation. This critical edition of Itinerarium reproduces Fleetwood's text with annotations and a host of interpretive and contextualizing essays from leading scholars. Taken together, they constitute the definitive introduction to this remarkable discussion of regnant queenship, providing a valuable tool for understanding contemporary notions of and underlying fears concerning the efficacy and desirability of female rule in Elizabethan England.